Chemical compositions and biological activities of commiphora gileadensis: A review - Mokaizh, A. A.; Abdurahman, Nour Hamid; Rosli, Mohd Yunus; Al-Haiqi, Omer; Elnour, Ahmed A.M. (Estacao Vitivinicola Nacional, 2023)
Background: A significant medicinal plant with several medicinal applications is Commiphora gileadensis. Due to the C. gileadensis medicinal properties, such as anti-cancer, antibacterial, antioxidant, cytotoxic, and antiviral activities, secondary phytoconstituents of the plant are crucial for medicine. Objective: This review aims to identify the biological activities and chemical compositions of C. gileadensis. Method: Data for the study were gathered from book chapters, research articles, review articles, and conference papers as part of the study's review approach, which was based on a thorough search of the literature. Results: Based on the results obtained, it may be inferred that the chemical composition and lipid constituents of C. gileadensis extracts provide substantiation for their utilisation in traditional medicinal practises. The primary chemical constituents seen in the sample were β-pinene (7.0% ± 0.1%), cymene (13.6 ± 0.1%), α-pinene (14.4%), terpinen-4-ol (18.7 ± 0.1%), and sabinene (22.7 ± 0.1%). Additionally, the sample exhibited the presence of various lipids, including phosphatidylethanolamine (PE) at a concentration of 7.6%, hexosylceramide (Hex1Cer) at 18%, and ceramide (Cer) at 69%. Conclusion: As a result, this review presented an overview of C. gileadensis' biological activities and chemical compositions. The review suggests that more attention be paid to the leaves barks. It stems from C. gileadensis, as well as the type of extraction techniques and advanced characterization because extending research materials could lead to the discovery of novel bioactive components.